A 3-D geographic location routing protocol based on forward region adaptive. Issue 4 (21st April 2021) - Yuting, Lu
ABSTRACT: In the application environment of real wireless sensor networks (WSNs), the sensor node is located in a 3-D space. Therefore, the conical forwarding region-based geographical (CFRG) routing protocol is proposed. In order to reduce the number of redundant data packets and reduce the collision probability of data packages, CFRG will establish a conical forwarding region to limit the number of forwarding nodes. In the case of the void node problem (VNP), the node will adaptively adjust the volume of the conical forwarding region and expand the space of forwarding node selection, namely, solve the VNP by adjusting the conical forwarding region. The simulation result shows that such CFRG proposed is able to solve the VNP. Comparing with a similar 3-D routing protocol, CFRG can improve the performances of end-to-end transmission delay and data packet loss rate.